Demographic differences in public acceptance of waste-to-energy incinerators in China: High perceived stress group vs. low perceived stress group - Chen, Jiabin; He, Xinyao; Shen, Ye; Zhao, Yiwei; Cui, Caiyun; Liu, Yong (Frontiers in Psychology, 2022)
Demographic characteristics have been recognized as an important factor affecting public acceptance of waste-to-energy (WTE) incineration facilities. The current study explores the effects of perceived stress on demographic differences in public acceptance of WTE incineration facilities using data collected by a large-scale questionnaire survey (1066 samples) conducted in three second-tier cities in China. The result of data analysis using a T-test (one-way ANOVA) shows firstly that people with low perceived stress have higher public acceptance of WTE incineration facilities. Second, the influence of demographic characteristics (gender, educational attainment, and age) on public acceptance of WTE incineration facilities vary in different groups of perceived stress levels. The findings enrich the knowledge system related to demographic characteristics research on NIMBY infrastructure projects and provide the theoretical basis for the government to formulate more targeted policies about NIMBY infrastructure sitting.